tRNA modifications: necessary for correct tRNA-derived fragments during the recovery from stress? - Durdevic, Zeljko; Schaefer, Matthias R. (Bioessays, 2013)
Endonuclease-mediated tRNA fragmentation has been observed in many species suggesting functional importance for tRNA fragments. The size distribution of tRNA-derived fragments indicates the existence of mechanisms that protect tRNAs and their fragments from total degradation by exonucleases. Could post-transcriptional modifications be important for the controlled processing of tRNAs?
Gesehen am 05.01.2021